Bundled Climate-Smart Innovations for Small Ruminants in Ethiopia - Ewell, Hanna; Haile, Aynalem; Getachew, Tesfaye; Makonnen, Brook T.; Ambaw, Gebermedihin; Solomon, Dawit; Girvetz, Evan (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
◼ CBBPs shift genetic improvement to communities—farmers co-manage data, selection, and sires—yielding cumulative benefits in productivity, income, and resilience. Mature sites can produce ~126 breeding sires annually, translating into ~14,000 sale-ready animals, with improvements aligned to local agroecologies and climate risks. ◼ The SmaRT pack (breeding, feeding, animal health, marketing, digital data) couples the core innovation with valuechain complements. Effective expansion depends on coordinated roles across MoA, ICARDA, regional bureaus, universities, cooperatives, finance and private actors, supported by standardized training, offline-capable registries, and a national breeding platform. ◼ A phased 2025–2030 roadmap prioritizes technical quality, demand, and investment (including revolving funds, PPPs, public budgets, and emerging carbon finance), as well as sustained use through policy integration and governance that prevents elite capture. Gender- and youth-responsive delivery (female extension, tailored finance) and context-specific tailoring across highland/lowland systems are essential to reach ~0.93M households toward 60% coverage.